2022
DOI: 10.1177/00469580221087881
|View full text |Cite
|
Sign up to set email alerts
|

Rabies-Related Knowledge, Attitudes, and Practices Among Primary School Students in Chonburi Province, Thailand

Abstract: In Thailand, rabies is an endemic fatal viral zoonosis where 40% of those infected are under age 15. The aim of this rabies KAP study (Knowledge, Attitudes, and Practices) is to examine preventive behaviors. A multistage sampling technique was employed for selecting the sample. Of 290 primary school students, 52.1% of them had poor knowledge, 89% had favorable attitudes, and 52.1% exercised proper preventive behaviors. We employed structural equation modeling to verify the systemic relationships and found rabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(29 reference statements)
3
3
1
Order By: Relevance
“…The study revealed that the pooled prevalence of a good level of rabies knowledge was estimated to be 62.24%, with individual estimates ranging from 7.50% ( 39 ) in the Addis Ababa survey to 99.25% in the Gondar Zuria area ( 51 ). The present combined prevalence of a good level of knowledge about rabies is congruent with a recent systematic review in Ethiopia ( 57 ), individual study reports in Nigeria ( 58 ), and Morocco ( 59 ) and is higher than research reports from Thailand (52.1%) ( 60 ), Mozambique, Limpopo National Park (18.9%), Bangladesh (58%) ( 61 ), and China (56.85%) ( 62 ). Such a level of adequate rabies knowledge in Ethiopia is not surprising, given that dog-mediated rabies cases were reported up to an estimated cumulative incidence of 89.8 per 100,000 population in the Tigray region of northern Ethiopia ( 6 ) and dog-mediated rabies is endemic in our country.…”
Section: Discussionsupporting
confidence: 88%
“…The study revealed that the pooled prevalence of a good level of rabies knowledge was estimated to be 62.24%, with individual estimates ranging from 7.50% ( 39 ) in the Addis Ababa survey to 99.25% in the Gondar Zuria area ( 51 ). The present combined prevalence of a good level of knowledge about rabies is congruent with a recent systematic review in Ethiopia ( 57 ), individual study reports in Nigeria ( 58 ), and Morocco ( 59 ) and is higher than research reports from Thailand (52.1%) ( 60 ), Mozambique, Limpopo National Park (18.9%), Bangladesh (58%) ( 61 ), and China (56.85%) ( 62 ). Such a level of adequate rabies knowledge in Ethiopia is not surprising, given that dog-mediated rabies cases were reported up to an estimated cumulative incidence of 89.8 per 100,000 population in the Tigray region of northern Ethiopia ( 6 ) and dog-mediated rabies is endemic in our country.…”
Section: Discussionsupporting
confidence: 88%
“…Hence, these factors should be captured in rabies education programmes. This study has also revealed that a greater proportion of dog owners with higher levels of rabies knowledge had attitudes and engaged in practices associated with lower rabies risk, as similarly reported by two previous studies [31,32] . Organising programmes aimed at improving rabies knowledge and ensuring behavioural changes in various settings, such as schools and communities, will immensely contribute to rabies prevention and control.…”
Section: Discussionsupporting
confidence: 85%
“…Others are more pathogen specific (Table 1 ). As a disease related to poverty, individuals, such as children, may not fundamentally understand how rabies is acquired or may not appreciate its severity (Laorujisawat et al 2022 ; Mapatse et al 2022 ; Zucca et al 2021 ). Even if a bite is reflected as a risk factor for disease acquisition, less serious or nonbite exposures may be ignored or not be recognized, such as related to bats, even in highly developed countries (Holzbauer et al 2023 ; Ma et al 2023 ).…”
Section: Resolute Burden Estimatesmentioning
confidence: 99%